Identification and Modeling of a GT-A Fold in the α-Dystroglycan Glycosylating Enzyme LARGE1 - Righino, Benedetta (J Chem Inf Model, 2020)
[Image: see text] The acetylglucosaminyltransferase-like protein LARGE1 is an enzyme that is responsible for the final steps of the post-translational modifications of dystroglycan (DG), a membrane receptor that links the cytoskeleton with the extracellular matrix in the skeletal muscle and in a variety of other tissues. LARGE1 acts by adding the repeating disaccharide unit [-3Xyl-α1,3GlcAβ1-] to the extracellular portion of the DG complex (α-DG); defects in the LARGE1 gene result in an aberrant glycosylation of α-DG and consequent impairment of its binding to laminin, eventually affecting the connection between the cell and the extracellular environment. In the skeletal muscle, this leads to degeneration of the muscular tissue and muscular dystrophy. So far, a few missense mutations have been identified within the LARGE1 protein and linked to congenital muscular dystrophy, and because no structural information is available on this enzyme, our understanding of the molecular mechanisms underlying these pathologies is still very limited. Here, we generated a 3D model structure of the two catalytic domains of LARGE1, combining different molecular modeling approaches. Furthermore, by using molecular dynamics simulations, we analyzed the effect on the structure and stability of the first catalytic domain of the pathological missense mutation S331F that gives rise to a severe form of muscle–eye–brain disease.